Inventário de Depressão de Beck - BDI: validação fatorial para mulheres com câncer Beck Depression Inventory - BDI: factorial analysis for women with cancer - Rita de Cássia Gandini; Maria do Carmo Fernandes Martins; Marjorie de Paula Ribeiro; Daniela Torres Gonçalves Santos (Psico-USF, 2007)
Este estudo teve por objetivo validar fatorialmente o Inventário de Depressão de Beck - BDI para uma amostra de 208 mulheres com câncer. A validação fatorial do BDI foi realizada por meio da análise fatorial, método de extração dos componentes principais e rotação oblimin, tendo sido identificadas duas soluções fatoriais, uma bifatorial - sendo F1 composto por 8 itens (a = 0,82) denominado "visão negativa de si mesmo", explicando 32,4% da variância e F2 com 5 itens (a = 0,77) denominado "função física", explicando 8% da variância - e outra unifatorial com 13 itens, com fidedignidade altamente satisfatória (a = 0,86) denominada "depressão", explicando 38% da variância total. This study refers to the factor analysis of the Beck Depression Inventory - BDI in a population composed by 208 women with cancer. The extraction method was principal components and the rotation procedure was oblimin. The BDI factorial analysis was done through the oblimin rotation, finding two solutions possibilities. One with two factors solution - the first one with 8 items (a = 0,82), called "negative view of self", explaining 32,4% of the variance and the second factor with 5 items (a = 0,77), called "physical function", explaining 8% of the variance - and other with one factor solution with 13 items, with really satisfactory reliability of 0,86, called "depression" and explaining 38% of the total variance.